Ultrahigh-manganese 500MPa-grade low-temperature aseismic steel bar and production method thereof
Through the chemical composition design and production process of ultra-high manganese 500MPa grade low-temperature seismic steel bars, the problem of high cost of Ni-based low-temperature steel bars is solved, high strength and high toughness in low-temperature environments are achieved, and the application range of low-temperature steel bars is expanded.
Patent Information
- Application Number
- CN202510069921.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The Ni element used in existing low-temperature steel bars is high in use, and the Ni-based low-temperature steel bars are expensive and difficult to widely use on rebars. It is necessary to develop a more economical and excellent low-temperature seismic steel bar.
Ultra-high manganese 500MPa grade low-temperature seismic steel bars are used to control chemical composition and production processes, including smelting, LF refining, VD vacuum degassing, continuous casting and bar rolling, to ensure that the steel bar structure is austenite, V-Nb microalloy is added, grains are refined, and toughness and strength are improved.
It achieves good low-temperature performance in the range of -165℃ to -196℃, has high yield strength, good plastic toughness, low notch sensitivity, and low cost, replacing expensive Ni-based low-temperature steel bars.
Smart Images

Figure CN119824317A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of low-temperature earthquake-resistant steel bars, and specifically relates to an ultra-high manganese 500MPa-grade low-temperature earthquake-resistant steel bar and a production method thereof. Background Art
[0002] Low temperature steel bars are mainly used in various low temperature storage tank reinforced concrete structures to support and reinforce the tanks. They also protect the tanks from leaking low temperature liquids. They are not in direct contact with low temperature liquids. -165℃ low temperature steel bars are used in the outer reinforced concrete structure of liquefied natural gas storage tanks.
[0003] Low temperature steel is mostly Ni-based low temperature steel (Ni content 0.5% to 9%), which relies on Ni solid solution in steel to improve the low temperature toughness of steel. At present, the Ni content in domestic -165℃ low temperature steel bars is about 1.0%. For example, Chinese patent CN103225044A discloses a vanadium microalloyed low temperature steel bar and its rolling process, CN
[0004] 110904390A discloses a niobium-vanadium composite microalloyed 600MPa grade low-temperature steel bar and its production method, CN 110669995 A discloses a hot-rolled ultra-low-temperature steel bar and its preparation method, and CN 110923413A discloses a vanadium microalloyed 600MPa grade low-temperature steel bar and its production method. Ni is a precious metal with limited resources. The cost of Ni-based low-temperature steel has always been high due to the addition of a large amount of Ni elements. It is very necessary to reduce the use of Ni elements in low-temperature steel.
[0005] In addition to being used in wear-resistant steel and automotive plates, in recent years, researchers have tried to use ultra-high manganese austenitic steel as low-temperature steel to replace expensive metal materials such as 9Ni steel and invar alloy, reduce costs and expand the scope of use of low-temperature steel. The use of Mn elements instead of Ni elements in low-temperature steel plays a role in improving the low-temperature stability of austenite, which can not only greatly reduce the cost of low-temperature steel, but the addition of Mn elements can also increase the solid solubility of N elements in austenite, making it have higher low-temperature strength.
[0006] Ultra-high manganese austenitic steel has an austenite structure at room temperature, has high toughness under low temperature conditions, and has high yield strength under low temperature conditions. It can be used as a structural material under low temperature conditions. At present, ultra-high manganese austenitic steel is gradually used in plates to replace 9Ni steel and invar alloy plates, but it is not used in rebar. Therefore, it is very meaningful to develop ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bars, which can save nickel resources, reduce production costs, and have higher safety. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides an ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar and a production method thereof, which is used for the construction of storage tanks for liquefied natural gas and the like at any temperature in the temperature range of -165°C to -196°C. The performance is better than the existing 500MPa grade -165°C low-temperature steel bars, while saving the consumption of precious alloy nickel and having lower costs.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] The invention discloses an ultra-high manganese 500MPa low-temperature earthquake-resistant steel bar, wherein the chemical composition and weight percentage of the ultra-high manganese 500MPa low-temperature earthquake-resistant steel bar are as follows: C 0.45%-0.55%, Si 0.20%-0.60%, Mn 21.0%-24.0%, V0.07%-0.13%, Nb 0.01%-0.03%, Alt 0.02%-0.05%, N 0.015%-0.025%, P≤0.015%, S≤0.005%, O≤0.0020%, H≤0.0002%, and the rest are Fe and other inevitable impurities; wherein, 33.5C%+Mn%≥35, 33.5C%-Mn%≤0, 3.3≤V / N≤6.0.
[0010] The metallographic structure of the ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar is austenite.
[0011] The yield strength R of the ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar eL ≥500MPa, tensile strength R m ≥650MPa, strength-to-yield ratio R m / R eL ≥1.30, elongation after fracture A≥45.0%, total elongation at maximum force A gt ≥40.0%.
[0012] The yield strength R of the ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar at -165°C eL ≥780MPa, unnotched maximum force total elongation A gt ≥29.0%, total elongation at maximum notch force A gt ≥10.0%, notch sensitivity index NSR≥1. Where NSR = tensile strength R of notched specimen m / Yield strength R of unnotched specimen eL .
[0013] The yield strength R of the ultra-high manganese 500MPa low-temperature earthquake-resistant steel bar at -196°C eL ≥830MPa, unnotched maximum force total elongation A gt ≥26.0%, total elongation at maximum notch force Agt ≥8.5%, notch sensitivity index NSR≥1.
[0014] The present invention also provides a production method of the ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar, which comprises the following steps: smelting → LF refining → VD vacuum degassing → continuous casting → heating → bar rolling → controlled cooling;
[0015] In the LF refining step, the basicity of the refined slag is 3-6, and the white slag time is ≥15 minutes;
[0016] In the VD vacuum degassing step, the vacuum degree is 67Pa and the time is ≥10 minutes;
[0017] In the heating step, the heating temperature is controlled at 1150-1200° C., the heating time is ≥90 minutes, and the soaking time is ≥25 minutes;
[0018] In the controlled cooling step, the temperature of the upper cooling bed is 1000-1050°C.
[0019] In the smelting step, high carbon ferromanganese and medium carbon ferromanganese alloy are smelted in a medium frequency furnace, molten iron and scrap steel are smelted in a converter, and the molten steel smelted in the converter is blended with the alloy solution melted in the medium frequency furnace and then refined in a LF furnace.
[0020] Furthermore, in the alloy solution, the percentage of manganese is 77-78.0%, and the percentage of carbon is 0.5-0.60%; the percentage of C at the converter end point is ≤0.10%, and the percentage of P is ≤0.010%.
[0021] In the continuous casting step, full protection casting is adopted, and the cooling water flow rate of the crystallizer is 105-120m 3 / h, secondary cooling water volume 0.50~0.65l / kg, pulling speed 1.9~2.3m / min.
[0022] In the bar rolling step, the starting rolling temperature is 1100-1150°C, and the finishing rolling temperature is 1020-1080°C.
[0023] In the ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar provided by the present invention, the functions and controls of the various components are as follows:
[0024] C and Mn: Carbon has a significant effect on the mechanical properties of ultra-high manganese steel. Carbon has the effect of solid solution strengthening and promoting the formation of single-phase austenite structure in ultra-high manganese steel. During hot rolling, the higher the carbon content, the higher the strength of the steel within a certain range, and the hardness continues to increase with the increase of carbon content. Manganese is the main element for stabilizing austenite, and both manganese and carbon can improve the stability of austenite. When the manganese content is less than 8%, all austenite and ferrite structures cannot be obtained. When the carbon content in the steel is constant, as the manganese content increases, the structure of the steel gradually changes from pearlite to martensite and further to austenite.
[0025] Carbon and manganese in steel should meet a certain ratio relationship, and a stable austenite structure can be obtained at room temperature. The content of carbon and manganese should meet the following requirements: 33.5C%+Mn%≥35 and 33.5C%-Mn%≤0. If 33.5C%+Mn%<35, the ferromagnetic phase a martensite structure will be formed, mainly because the stability of the austenite structure cannot be guaranteed, so that the austenite in the organization cannot get the required amount. If 33.5C-Mn>0, it is mainly because when the C content is too high, carbides are easily formed around the austenite grain boundaries, which causes some physical properties to deteriorate sharply. Therefore, the C and Mn contents must be controlled within a certain range. If they cannot be controlled, the austenite content will be insufficient and carbides will be formed. Therefore, the C content is between 0.45% and 0.55%. The Mn content is between 21.0% and 24.0%.
[0026] Si: Si is the main deoxidizing element in steel, and as a solid solution hardening element, it helps to improve the strength. With the increase of silicon content, the amount of carbides on the rolled grain boundaries increases and becomes coarser. After the carbides are dissolved, the grain boundaries remain microscopically loose, which easily forms micro crack sources. Silicon can be dissolved in austenite in ultra-high manganese steel, playing a role in solid solution strengthening. At the same time, silicon changes the solubility of carbon in austenite. Therefore, the Si content is controlled to be 0.20% to 0.60%.
[0027] V: Adding vanadium to steel can refine the grain structure and improve strength and toughness. V forms V (C, N) precipitation phase with N and C elements in steel, which has a strong precipitation strengthening effect. The diffusion of V is inhibited during the phase change process, resulting in a large amount of V solid solution in the steel. The solid solution of V can significantly inhibit the diffusion of C during the phase change process, which can refine the grain and improve the strength of the steel. Excessive V content will result in high cost, so the V content is controlled at 0.07% to 0.13%.
[0028] Nb: Nb can significantly refine austenite grains. Grain refinement can not only improve the toughness of steel, but also improve the delayed fracture resistance of high-strength steel. The Nb content cannot be too high. Too much Nb will promote bainite transformation, increase the bainite content, and reduce the plasticity of steel. Therefore, the range of Nb is controlled at 0.01% to 0.03%.
[0029] Alt: Alt is a strong deoxidizing element and improves the oxidation resistance of steel. Alt can also refine austenite grains and improve delayed fracture resistance. In addition, the present invention adds a relatively high amount of Alt to combine with nitrogen to form AlN, which reduces the pinning effect of dislocations and improves impact toughness. The Alt content is controlled at 0.02% to 0.05%.
[0030] S and P: Impurity elements such as S and P will segregate at the grain boundaries, which will greatly reduce the delayed fracture resistance. The S element forms MnS inclusions and segregates at the grain boundaries, thereby increasing the delayed fracture sensitivity of the steel, thus controlling the lower sulfur content in the steel.
[0031] Phosphorus in ultra-high manganese steel is a common harmful element. The segregation of phosphorus is directly related to the carbon content in the steel. The higher the carbon content in austenite, the lower the solubility of phosphorus, making it easier to precipitate in the form of phosphorus eutectic after solidification. Due to the serious segregation of phosphorus, it is easy to enrich in local areas of the steel to form a phosphorus eutectic structure with a high phosphorus content. When there is more phosphorus in the steel, it will also affect other elements, such as the increase in the segregation degree of carbon and manganese elements. Therefore, the P and S contents are controlled at S≤0.005% and P≤0.015%.
[0032] N: During the solidification process, V and N in ultra-high manganese steel can form VN and V(C, N), and become non-spontaneous crystallization cores to refine the cast structure grains. At the same time, the VN and V(C, N) particles precipitated at the grain boundaries can inhibit the growth of ultra-high manganese steel grains during heating, significantly improve the grain size of ultra-high manganese steel, and thus improve the strength and toughness of ultra-high manganese steel. There is a certain matching relationship between the N content and the V content in the steel, which can give full play to the microalloying effect of V, so N is controlled at 0.015-0.025%.
[0033] O: Oxygen forms various oxide inclusions in steel. Under the action of stress, stress concentration is easily generated at these oxide inclusions, leading to the initiation of microcracks, thereby deteriorating the mechanical properties of steel, especially toughness and fatigue resistance. Therefore, measures must be taken in metallurgical production to reduce its content as much as possible to control TO≤0.0020%;
[0034] H: The harm of H element in steel is mainly manifested in causing "hydrogen embrittlement", "white spots", point segregation, static fatigue fracture and other serious defects, which reduce the plasticity of steel and increase its brittleness, and cause sudden brittle fracture of steel structures or steel parts under stress below the ultimate strength. Therefore, the H content is controlled at H≤0.0002%.
[0035] The present invention adopts a VN and Nb composite microalloying scheme to refine the original austenite grain size, which can improve the strength and toughness at the same time, and can also act as a hydrogen trap to inhibit the diffusion of hydrogen and make hydrogen uniformly distributed, improve the resistance to hydrogen-induced delayed fracture, and improve the low-temperature performance of steel bars; and fully utilize the solid solution V in austenite to inhibit the diffusion of C to refine the size of austenite ferrite, thereby ensuring high strength and toughness and high strength-to-yield ratio. In order to obtain a fine-grained austenite structure, the chemical composition must meet 3.3≤V / N≤6.0.
[0036] In order to obtain a stable austenite structure at room temperature, the present invention adopts ultra-high manganese component design, reasonable C and Mn matching, combines the hot-rolled threaded steel rolling process, selects a suitable micro-alloying scheme, and rolling heating, controlled rolling and controlled cooling processes to produce 500MPa-grade low-temperature earthquake-resistant steel bars with an austenite structure at room temperature, which have good low-temperature properties at room temperature and at any temperature in the temperature range of -165°C to -196°C.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar provided by the present invention has a microstructure of austenite at room temperature, and its room-temperature mechanical properties are: yield strength R eL ≥500MPa, tensile strength R m ≥650MPa, strength-to-yield ratio R m / R eL ≥1.30, elongation after fracture A≥45.0%, total elongation at maximum force A gt ≥40.0%. Low temperature mechanical properties within the temperature range of -165℃~-196℃: Yield strength R at -165℃ eL ≥780MPa, unnotched maximum force total elongation A gt ≥29.0%, total elongation at maximum notch force A gt ≥10.0%, notch sensitivity index NSR≥1; yield strength R at -196℃ eL ≥830MPa, unnotched maximum force total elongation A gt ≥26.0%, total elongation at maximum notch force A gt ≥8.5%, notch sensitivity index NSR≥1, with good strength and plasticity, and low notch sensitivity at any low temperature in the range of -165℃~-196℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The metallographic structure diagram of the surface of the 500MPa low-temperature earthquake-resistant steel bar in Example 1;
[0040] Figure 2The metallographic structure diagram of the surface of the 500MPa low-temperature earthquake-resistant steel bar in Example 1;
[0041] Figure 3 This is the metallographic structure diagram of the core of the 500MPa low-temperature earthquake-resistant steel bar in Example 1;
[0042] Figure 4 This is the metallographic structure diagram of the core of the 500MPa grade low-temperature earthquake-resistant steel bar in Example 1. DETAILED DESCRIPTION
[0043] The invention provides an ultra-high manganese 500MPa low-temperature earthquake-resistant steel bar. The chemical composition and weight percentage of the ultra-high manganese 500MPa low-temperature earthquake-resistant steel bar are: C 0.45%-0.55%, Si 0.20%-0.60%, Mn 21.0%-24.0%, V 0.07%-0.13%, Nb 0.01%-0.03%, Alt0.02%-0.05%, N 0.015%-0.025%, P≤0.015%, S≤0.005%, O≤0.0020%, H≤0.0002%, and the rest are Fe and other inevitable impurities; wherein, 33.5C%+Mn%≥35, 33.5C%-Mn%≤0, 3.3≤V / N≤6.0.
[0044] The production method of the ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar is as follows:
[0045] (1) Medium frequency furnace smelting: melt high carbon ferromanganese and medium carbon ferromanganese alloy, the alloy amount is 27% of the normal molten steel per furnace, adjust the ratio of high carbon ferromanganese and medium carbon ferromanganese to meet the manganese content of the alloy solution after melting to 77% to 78.0%, and add carbon powder to control the carbon content of the alloy solution to 0.5% to 0.60%.
[0046] (2) Converter smelting: Add molten iron and scrap steel for smelting, the tapping volume is controlled at 73% of the normal molten steel volume per furnace, the converter end point C is controlled to be ≤0.10%, P ≤0.010%; slag blocking tapping, add refined slag and lime when about 1 / 5 of the molten steel is tapped, add deoxidizer and alloy when about 1 / 3 of the steel is tapped, the order is: aluminum iron → carbon powder → vanadium nitrogen → silicon manganese, after the tapping is completed, according to the amount of slag, evenly sprinkle an appropriate amount of aluminum particles on the slag surface. Add the amount of silicon manganese alloy according to the silicon content target, and the carbon content target of the molten steel after tapping is 0.45%.
[0047] (2) LF furnace refining: The molten steel from the converter is mixed with the alloy solution melted in the medium frequency furnace and then sent to the LF furnace for refining. Argon is blown from the bottom of the ladle throughout the process, and the argon flow rate is based on the molten steel not splashing out of the ladle. Pre-melted refining slag and lime are added to make slag, with a basicity R of 3-6 and a white slag time of ≥15 minutes. According to the composition analysis results before entering the LF furnace, alloys are added before and during refining to adjust the contents of C, Si, Mn, V, Nb, and Al.
[0048] (3) VD vacuum degassing: vacuum degree 67Pa holding time ≥ 10 minutes. If the composition is adjusted, the vacuum holding time must be guaranteed to be more than 5 minutes after the adjustment. After breaking the vacuum, calcium line treatment is carried out. Bottom nitrogen blowing treatment is carried out before leaving the station to ensure that the nitrogen content in the molten steel meets the requirements.
[0049] (4) Billet continuous casting: Billet continuous casting is adopted. Full protection casting is adopted. A protective sleeve + argon seal is used between the ladle and the tundish. The tundish uses a molten steel covering agent and argon blowing protection. An integral immersion nozzle is used between the tundish and the crystallizer. A weak cooling process is adopted. The crystallizer cooling water flow rate is 105-120m 3 / h, the secondary cooling water volume is 0.50~0.65l / kg, low casting speed is adopted, and the casting speed is 1.9~2.3m / min to obtain defect-free ingots.
[0050] (5) Bar rolling: The present invention can achieve In order to meet the needs of the rolling process and to make the carbon and nitrides of V and Nb dissolved in austenite, the heating temperature is controlled at 1150-1200℃, the heating time is greater than 90 minutes, and the soaking time is greater than 25 minutes to ensure that the elements of Mn, Nb and V are fully dissolved. The heated ingot enters the continuous rolling unit for rolling, with the starting rolling temperature of 1100-1150℃, the finishing rolling temperature of 1020-1080℃, and the higher final rolling temperature to ensure the uniformity of the composition structure. After rolling, weak water cooling is performed to cool to the upper cooling bed temperature of 1000-1050℃, and the cooling bed is air-cooled, so as to obtain a properly fine austenite structure and improve the plasticity, toughness and strength-to-yield ratio of the invention steel.
[0051] The present invention is described in detail below with reference to the embodiments.
[0052] The chemical composition and weight percentage of the hot-rolled steel bars in each embodiment and comparative example are shown in Table 1, and the remainder is iron and unavoidable impurities.
[0053] Table 1
[0054]
[0055]
[0056] The steelmaking, continuous casting and billet rolling processes of the steel bars in each embodiment and comparative example are shown in Table 2.
[0057] Table 2 Steelmaking process
[0058]
[0059]
[0060] The bar rolling processes of the embodiments of the present invention and the comparative examples are shown in Table 3.
[0061] Table 3 Rolling process
[0062]
[0063]
[0064] The room temperature and low temperature mechanical properties of the steel bars in the embodiments and comparative examples are shown in Tables 4 and 5.
[0065] Table 4 Mechanical properties at room temperature
[0066]
[0067] Table 5 Low temperature performance
[0068]
[0069]
[0070] The low-temperature steel bars produced by the method of the present invention all retain austenite structure at room temperature, and through microalloying and rolling controlled cooling, the austenite grains are refined, and the best match between strength and yield ratio is achieved, with the yield ratio reaching more than 1.30, while having good low-temperature performance. Figure 1 and Figure 2 , is austenite structure, the core microstructure is Figure 3 and Figure 4 , which is an austenitic structure.
[0071] The carbon and manganese contents in the ingredients of Comparative Example 1 cannot meet the requirements of the present invention, and a stable austenite structure cannot be obtained. The room temperature yield strength, tensile strength, -165℃ notched and unnotched sample A gt , -196℃ notched and unnotched specimens A gt The requirements of the present invention are not met;
[0072] In Comparative Example 2, Nb is not added to the components. Even though it is produced according to the process of the present invention, the yield strength at room temperature is low and cannot meet the performance requirements of the present invention.
[0073] The V content in the components of Comparative Example 3 is relatively low. Even if it is produced according to the process of the present invention, the yield strength at room temperature is low and cannot meet the performance requirements of the present invention.
[0074] Although the ingredients of Comparative Example 4 meet the requirements of the present invention, the VD vacuum holding time during production does not meet the requirements of the present invention, resulting in the oxygen content in the steel not meeting the requirements of the present invention, and the elongation of the steel deteriorates. gt , -165℃ notched and unnotched A gt , -196℃ notched and unnotched A gt All do not meet the requirements of the present invention.
[0075] Although the ingredients of Comparative Example 5 meet the requirements of the present invention, the heating temperature, heating time and soaking time in production do not meet the requirements of the present invention, resulting in poor solid solution effect of micro-alloying elements and the yield strength at room temperature does not meet the requirements of the present invention.
[0076] Although the ingredients of Comparative Example 6 meet the requirements of the present invention, the temperature of the upper cooling bed in production does not meet the requirements of the present invention. The cooling speed after rolling is fast, resulting in the structure of the steel being bainite + a small amount of martensite, and the elongation performance is poor. gt , -165℃ notched and unnotched A gt , -196℃ notched and unnotched A gt , NSR do not meet the requirements of the present invention.
[0077] It can be seen from Table 4 that the seismic steel bars produced according to the scheme of the present invention have room temperature mechanical properties that can reach: yield strength R eL ≥500MPa, tensile strength R m ≥650MPa, strength-to-yield ratio R m / R eL ≥1.30, elongation after fracture A≥45.0%, total elongation at maximum force A gt ≥40.0%.
[0078] It can be seen from Table 5 that the low-temperature mechanical properties of the earthquake-resistant steel bars produced according to the scheme of the present invention can reach: the yield strength R at -165°C eL ≥780MPa, unnotched maximum force total elongation A gt ≥29.0%, total elongation at maximum notch force A gt ≥10.0%, notch sensitivity index NSR≥1; yield strength R at -196℃ eL ≥830MPa, unnotched maximum force total elongation A gt ≥26.0%, total elongation at maximum notch force A gt ≥8.5%, notch sensitivity index NSR≥1.
[0079] The detailed description of an ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar and its production method with reference to the above-mentioned embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. An ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar, characterized in that: The chemical composition and weight percentage of the ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar are: C 0.45%-0.55%, Si 0.20%-0.60%, Mn 21.0%-24.0%, V 0.07%-0.13%, Nb 0.01%-0.03%, Alt0.02%-0.05%, N 0.015-0.025%, P≤0.015%, S≤0.005%, O≤0.0020%, H≤0.0002%, and the rest are Fe and other inevitable impurities; wherein, 33.5C%+Mn%≥35, 33.5C%-Mn%≤0, 3.3≤V / N≤6.
0.
2. The ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar according to claim 1, characterized in that: The metallographic structure of the ultra-high manganese 500MPa grade low-temperature earthquake-resistant steel bar is austenite.
3. The ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar according to claim 1, characterized in that: The yield strength R of the ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar eL ≥500MPa, tensile strength R m ≥650MPa, strength-to-yield ratio R m / R eL ≥1.30, elongation after fracture A≥45.0%, total elongation at maximum force A gt ≥40.0%。 4. The ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar according to claim 1, characterized in that: The yield strength R of the ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar at -165°C eL ≥780MPa, unnotched maximum force total elongation A gt ≥29.0%, total elongation at maximum notch force A gt ≥10.0%, notch sensitivity index NSR≥1.
5. The ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bar according to claim 1, characterized in that: The yield strength R of the ultra-high manganese 500MPa low-temperature earthquake-resistant steel bar at -196°C eL ≥830MPa, unnotched maximum force total elongation A gt ≥26.0%, total elongation at maximum notch force A gt ≥8.5%, notch sensitivity index NSR≥1.
6. The method for producing ultra-high manganese 500MPa grade low temperature earthquake-resistant steel bars according to any one of claims 1 to 5, characterized in that: The production method comprises the following steps: smelting → LF refining → VD vacuum degassing → continuous casting → heating → bar rolling → controlled cooling; In the LF refining step, the basicity of the refined slag is 3-6, and the white slag time is ≥15 minutes; In the VD vacuum degassing step, the vacuum degree is 67Pa and the time is ≥10 minutes; In the heating step, the heating temperature is controlled at 1150-1200° C., the heating time is ≥90 minutes, and the soaking time is ≥25 minutes; In the controlled cooling step, the temperature of the upper cooling bed is 1000-1050°C.
7. The production method according to claim 6, characterized in that: In the smelting step, high carbon ferromanganese and medium carbon ferromanganese alloy are smelted in a medium frequency furnace, molten iron and scrap steel are smelted in a converter, and the molten steel smelted in the converter is blended with the alloy solution melted in the medium frequency furnace and then refined in a LF furnace.
8. The production method according to claim 7, characterized in that: In the alloy solution, the percentage of manganese is 77-78.0%, and the percentage of carbon is 0.5-0.60%; the percentage of C at the converter end point is ≤0.10%, and the percentage of P is ≤0.010%.
9. The production method according to claim 6, characterized in that: In the continuous casting step, full protection casting is adopted, and the cooling water flow rate of the crystallizer is 105-120m 3 / h, secondary cooling water volume 0.50~0.65l / kg, pulling speed 1.9~2.3m / min.
10. The production method according to claim 6, characterized in that: In the bar rolling step, the starting rolling temperature is 1100-1150°C, and the finishing rolling temperature is 1020-1080°C.
Citation Information
Patent Citations
Steel for vanadium micro alloying low temperature steel bar and process for rolling steel
CN103225044A
Hot-rolling ultra-low-temperature rebar and preparation method thereof
CN110669995A
Steel for vanadium micro-alloyed 600 MPa grade low-temperature steel bar and production method thereof
CN110923413A
Steel sheet for low-temperature service having excellent surface processing quality and method for manufacturing same
CN107109602A
Design of high-manganese medium-thickness plate applied to LNG (Liquefied Natural Gas) storage tanks and production method thereof
CN107177786A